2019
DOI: 10.26803/ijlter.18.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of First-Grade Students’ Literacy and Numeracy Levels and the Influence of Key Factors

Abstract: The acquisition of literacy and numeracy in early years education provides children with an essential skill for learning and life. This study aims to assess the literacy and numeracy skills of firstgraders in Qatari governmental schools. It also determines whether there is a relationship between numeracy skills and literacy skills and whether these are influenced by such factors as parents' educational level, students' prior knowledge, and gender. Study participants included 80 students (21 male, 59 female). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…As we know that maternal education can play a vital role in the development of a child, we found in the study that mothers without education or primary education were less likely to develop their children's early literacy and numeracy skills compared to mothers with at least a secondary education. Another similar study conducted by Barham et al. (2019) in Qatar found that a first-grade student's literacy is influenced by her mother's education, but their numeracy is not always influenced.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As we know that maternal education can play a vital role in the development of a child, we found in the study that mothers without education or primary education were less likely to develop their children's early literacy and numeracy skills compared to mothers with at least a secondary education. Another similar study conducted by Barham et al. (2019) in Qatar found that a first-grade student's literacy is influenced by her mother's education, but their numeracy is not always influenced.…”
Section: Discussionmentioning
confidence: 89%
“…As we know that maternal education can play a vital role in the development of a child, we found in the study that mothers without education or primary education were less likely to develop their children's early literacy and numeracy skills compared to mothers with at least a secondary education. Another similar study conducted by Barham et al (2019) in Qatar found that a first-grade student's literacy is influenced by her mother's education, but their numeracy is not always influenced. This finding is consistent with an earlier study in Bangladesh conducted by Alam et al (2021), which found that children with mothers who had completed secondary education or higher had a better chance of developing literacy and numeracy skills than children whose mothers had primary or no education.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the samples are small size and can limit the results. Apart from the interest in learning, factors that need to be considered in the achievement of literacy and numeracy in early childhood include self-regulation [54], home learning environment [55], teacher efficacy [56], educational level of parents [15], collaborative parent-child interactions [30], [57], and gender [15]. The factors mentioned above, although not analyzed or in the focus of this research, can be factors that can influence the results that can be taken into consideration in future research.…”
Section: Limitationmentioning
confidence: 99%
“…The term numeracy describes the capacity to comprehend, apply, and utilize mathematical ideas and techniques in a variety of settings [11], [12], [13]. It includes basic arithmetic operations, numerical reasoning, problem-solving, and the competence to successfully illuminate and communicate mathematical facts [14], [15], [16], [17]. For everyday tasks like handling personal finances, making wise decisions, and comprehending mathematical data in a variety of professions, numeracy abilities are essential.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-school stage is considered one of the most important stages in a child's life and the formation of his or her personality, as it gives the child an opportunity to gain experiences and knowledge (Aldridge & Goldman, 2007;Rababah, 2012;Al Shammari & Olaimat, 2019), to develop school readiness skills (Throndsen, Shumway, Moyer-Packenham, 2019), and acquisition of numeracy and literacy skills (Al Shammari & Olaimat, 2019;Barham, Ihmeideh, Al-Falasi, Alabdallah, 2019). Therefore, it is necessary to pay attention to language experiences and the process of preparing children for reading by providing exposure to necessary skills, especially before they are introduced to the actual reading stage (Dickinson & Tabors, 2001;Hashman, 2008;Mukdadi, Batiha, & Martín, 2016;Rababah, 2017).…”
Section: Introductionmentioning
confidence: 99%